Handling of Scabies in Domestic Cat at Q-one Petklinik Surabaya - Bagus Uda Palgunadi; Katarina Kole Grace Wangge; Lailia Dwi Kusuma Wardhani (Universitas Airlangga, 2021)
Background: Scabies is a skin disease caused by Sarcoptes scabiei. Scabies is transmitted through direct contact with animals affected by scabies or contact with the source of scabies mite in area of cat lives. Purpose: This study aims to determine the management of scabies at Q-One PetKlinik Surabaya. Method: Handling domestic cats affected by S.scabiei began with an interview with the owner and examinated with the physical condition of cats, and observed the body that was infected with S.scabiei. Scrabbing on scabs was conducted in the cat’s body which was located in the facial area, and followed by microscopic examination to observe the S.scabiei mite. Results: During April 2021, there were 13 domestic cats affected by scabies. Treatment for scabies was by administrated drugs containing 5% Permethrin. Cats were also given supportive therapy by grooming with antiectoparasite shampoo after two weeks from being given drugs. Conclusion: Handling cases of scabies in domestic cats at Q-One PetKlinik Surabaya is performed by cleaning the scab, applying an ointment containing 5% permethrin, and giving anti-histamine and anti-parasitic as well as providing supportive therapy in the form of grooming using shampoo containing anti-ectoparasites.